GMT composite material automobile roof and preparation method thereof

By adopting GMT composite car roof, the problem of thermal aging of PU substrates under high temperature conditions is solved, and better mechanical properties, antibacterial properties and riding comfort are achieved.

CN119749001AActive Publication Date: 2025-04-04YANTAI ZHENGHAI HIGH TECH

Patent Information

Application Number
CN202510258357.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-04
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

PU substrate car roof is prone to thermal aging when exposed to sunlight for a long time during high temperatures or long-term exposure, resulting in sticky surfaces, affecting aesthetics and service life.

Method used

The GMT composite car roof is used, including the GMT composite sheet layer, hot melt adhesive layer and fabric layer. The GMT composite sheet layer is composed of composite fiber felt, modified bamboo fiber, tea tree oil, etc., and has excellent mechanical properties, antibacterial properties and sound insulation properties.

Benefits of technology

GMT composite car roof has good mechanical properties, wear resistance and antibacterial properties, which can effectively block noise, improve riding comfort, and show better stability and durability under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of automobile parts, and particularly discloses a GMT composite material automobile roof and a preparation method thereof. The GMT composite material automobile roof comprises a GMT composite board layer, a hot melt adhesive layer and a fabric layer, and is characterized in that the GMT composite board layer comprises the following components in parts by weight; comprising the following raw materials: 90-100 parts of composite fiber felt, 22-30 parts of modified bamboo fiber, 3-5 parts of tea tree oil, 1-2 parts of sodium tripolyphosphate, 2-4 parts of beta-glycerophosphate disodium, 0.5-0.8 part of lecithin, 15-20 parts of modified talcum powder, 4-6 parts of an expandable microsphere foaming agent and 190-200 parts of deionized water. The GMT composite material automobile ceiling prepared in the invention has excellent mechanical strength, durability and aging resistance, can provide mechanical protection for parts, and prolongs the service life of the automobile ceiling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of automobile accessories, and in particular to a GMT composite material automobile roof and a preparation method thereof. Background Art

[0002] The car roof, also known as the roof system or canopy, is a key component of the car's interior. It is connected to the car body roof crossbeams, side panel inner skins, pillars, sun visors, safety handles, interior ceiling lights and other components, and has the functions of heat insulation and thermal insulation, sound insulation and sound absorption, and safety.

[0003] From a structural point of view, the car roof can be divided into a facing layer, an adhesive layer and a frame layer. The facing layer directly faces the passengers and is usually made of fabric, artificial leather, PVC film and other materials; the frame layer provides structural support and is usually made of metal, plastic or composite materials; the adhesive layer is used for the facing layer and the frame layer to make the car roof structure stable.

[0004] For the skeleton layer, PU-based ceiling is usually used, which has the advantages of light weight, wear resistance, sound insulation and noise reduction, high toughness, and not easy to crack or deform. However, under high temperature or long-term exposure to sunlight, the PU substrate may undergo thermal aging, causing the surface to become sticky, which in turn affects the appearance and service life. Summary of the invention

[0005] In order to improve the problem of thermal aging of PU substrates caused by long-term exposure to sunlight, the present application provides a GMT composite material automobile roof and a preparation method thereof.

[0006] The present application provides a GMT composite material automobile roof, which adopts the following technical solution: A GMT composite material automobile roof comprises a GMT composite sheet layer, a hot melt adhesive layer and a fabric layer, characterized in that the GMT composite sheet layer comprises the following raw materials, measured in parts by weight: 90-100 parts of composite fiber felt, 22-30 parts of modified bamboo fiber, 3-5 parts of tea tree oil, 1-2 parts of sodium tripolyphosphate, 2-4 parts of β-glycerophosphate disodium, 0.5-0.8 parts of lecithin, 15-20 parts of modified talc, 4-6 parts of expandable microsphere foaming agent, and 190-200 parts of deionized water.

[0007] By adopting the above technical solution, GMT is a glass fiber felt reinforced thermoplastic composite material. The GMT composite sheet layer serves as the main structural layer of the automobile roof. The GMT material is a composite material with thermoplastic resin as the matrix and glass fiber felt as the reinforcing skeleton. It has the advantages of light weight, toughness, rigidity, impact resistance and corrosion resistance. The GMT composite sheet layer plays a supporting and protective role in the automobile roof, can withstand certain external force impact, and has good sound absorption performance. It can effectively block the noise transmitted by the roof from entering the car, and absorb the noise generated in the car, thereby improving the ride comfort of the car.

[0008] The hot melt adhesive layer acts as a bonding layer between the GMT composite sheet layer and the fabric layer, which can firmly bond the two together to form an integral structure, thereby improving the strength and stability of the car roof. The fabric layer has certain air permeability and moisture absorption, which can maintain air circulation in the car, reduce humidity and stuffiness, and also help prevent the growth of bacteria and mites.

[0009] In the GMT composite board layer, the composite fiber felt is the main reinforcing skeleton, providing the mechanical properties and dimensional stability of the board. The modified bamboo fiber has excellent moisture absorption, air permeability and antibacterial properties, and can be embedded in the composite fiber felt structure to increase the antibacterial and air permeability of the composite fiber felt. Tea tree oil has antibacterial, anti-inflammatory, insect repellent and mite killing properties, which improves the antibacterial biological activity of the overall system. Sodium tripolyphosphate adjusts the pH of the overall system, helps to disperse and stabilize other ingredients, makes the various components mixed evenly, and improves the corrosion resistance of the board.

[0010] β-Glycerophosphate disodium has good biocompatibility, which makes the various components in the system mixed evenly, and lecithin helps to disperse tea tree oil. Modified talcum powder has good filling properties, reduces the density and cost of the board, while improving the hardness and wear resistance of the board, and improves its compatibility with the GMT matrix. The expandable microsphere foaming agent expands during heating to form a closed-cell structure, thereby improving the thermal insulation performance of the board and reducing its weight. The various components are evenly mixed, and the resulting GMT composite board layer has good mechanical properties, wear resistance and antibacterial properties.

[0011] Preferably, the method for preparing the modified bamboo fiber comprises the following steps: (1) dispersing the bamboo fiber in a NaOH solution, stirring for 1-2 hours, washing with water, and then dispersing the bamboo fiber in a silane coupling agent aqueous solution, adding calcium carbonate, ultrasonicating for 30-35 minutes, and drying to obtain pretreated bamboo fiber; (2) Dispersing the modified loofah fiber in deionized water, adding the pretreated bamboo fiber of step (1), stirring at a temperature of 60-65° C. for 2-3 h, adding glacial acetic acid, chitosan, and sorbitol, continuing to stir for 2-3 h, drying, and crushing to obtain modified bamboo fiber.

[0012] By adopting the above technical scheme, the NaOH solution softens the bamboo fiber and removes glue impurities in the bamboo fiber, thereby increasing the specific surface area of ​​the bamboo fiber. The washed bamboo fiber is dispersed in the aqueous solution of the silane coupling agent. The silane coupling agent can improve the compatibility of the bamboo fiber with other materials and enhance the bonding force between the bamboo fiber and other materials. Calcium carbonate can be loaded on the surface and pores of the bamboo fiber to enhance the rigidity and hardness of the bamboo fiber.

[0013] Modified loofah fiber is dispersed in deionized water. Loofah fiber has a natural porous structure, good mechanical strength and toughness. Modified loofah fiber can be fully combined with bamboo fiber. Modified loofah fiber and bamboo fiber are mutually loaded, which improves the mechanical properties, porosity and specific surface area of ​​bamboo fiber. Chitosan dispersed in deionized water has certain viscosity and film-forming properties, which makes the modified loofah fiber and bamboo fiber bond closely, increases the structural stability of modified bamboo fiber, and improves the flexibility, water resistance and biocompatibility of modified bamboo fiber. Sorbitol has good dispersibility, which makes each component in the system dispersed evenly, increases the structural stability of modified bamboo fiber, and subsequently modified bamboo fiber is applied to GMT composite material board to increase the comprehensive properties of GMT composite material board such as mechanical properties, wear resistance and bactericidal properties.

[0014] Preferably, the mass ratio of the bamboo fiber, the modified loofah fiber and chitosan is 1:0.5-0.6:0.1-0.2.

[0015] By adopting the above technical scheme, the mass ratio of bamboo fiber, modified loofah fiber and chitosan is further limited within a certain range, so as to improve the comprehensive performance of bamboo fiber. Bamboo fiber has high strength and good toughness. Modified loofah fiber and bamboo fiber can adsorb and combine with each other, so as to increase the mechanical properties and adsorption of bamboo fiber. Chitosan has certain viscosity and film-forming property, so that bamboo fiber and modified loofah fiber are closely bonded, and the flexibility of modified bamboo fiber is increased. Subsequently, it is applied to GMT composite material board to increase the mechanical strength, weather resistance and antibacterial property of GMT composite material board, so as to extend the service life of the board.

[0016] Preferably, the preparation method of the modified loofah fiber comprises the following steps: crushing the loofah fiber, dispersing it in a sodium hydroxide solution, stirring for 10-12 minutes, washing with water, dispersing it in hydrogen peroxide, stirring for 25-30 minutes, washing with water, dispersing it in deionized water, adding 3-chloro-2-hydroxypropyltrimethylammonium chloride, nano carbon powder, and hydroxypropyl methylcellulose, stirring for 3-4 hours at a temperature of 70-75° C., drying, filtering, and obtaining treated loofah fiber, and then spraying the adhesive mixture on the surface of the treated loofah fiber to obtain modified loofah fiber; The adhesive mixture is prepared by mixing deionized water, ethylene glycol, dextrin glue, lignin sulfonate and disodium ethylenediaminetetraacetate.

[0017] By adopting the above technical scheme, the crushed loofah fibers are dispersed in a sodium hydroxide solution to remove impurities such as lignin and hemicellulose in the loofah fibers and improve the roughness of the fiber surface; and then dispersed in hydrogen peroxide to further remove impurities in the loofah fibers and improve their surface properties.

[0018] The treated loofah fiber is dispersed in deionized water, and 3-chloro-2-hydroxypropyl trimethyl ammonium chloride, nano carbon powder, and hydroxypropyl methyl cellulose are added. 3-chloro-2-hydroxypropyl trimethyl ammonium chloride is used as a dispersant. Through its cationic part, it interacts with the negative charge on the surface of the loofah fiber and the nano carbon powder, reduces the agglomeration between particles, and enhances the dispersibility of these particles in water. The nano carbon powder has good mechanical properties, thermal stability and electrical conductivity, can be loaded on the surface and pores of the loofah fiber, effectively fills the gaps between fibers, forms a more compact structure, and increases the strength, wear resistance and toughness of the loofah fiber. The thickening and bonding force of hydroxypropyl methyl cellulose help the nano carbon powder to adhere to the surface of the loofah fiber, improve the comprehensive performance of the modified loofah fiber, and is subsequently applied to modified bamboo fiber to improve the mechanical properties, wear resistance, flexibility and antibacterial properties of the modified bamboo fiber.

[0019] The adhesive mixture is sprayed on the surface of the treated loofah fiber. The dextrin glue has high viscosity, and the lignin sulfonate has excellent adhesion and dispersibility. The combination with the dextrin glue improves the adhesion of the adhesive composition and helps the uniform distribution of the adhesive on the substrate. Disodium ethylenediaminetetraacetic acid improves the stability of the adhesive composition. The various components are mixed to improve the viscosity and dispersibility of the adhesive composition. The adhesive composition covers the treated loofah fiber, which not only makes the loofah fiber and the nano-carbon powder adhere tightly, but also increases the adhesion of the modified loofah fiber. It is subsequently applied to bamboo fiber to improve the adhesion between bamboo fiber and other components, which helps to improve the performance of GMT composite material boards.

[0020] Preferably, the method for preparing the modified talc comprises the following steps: (1) dispersing talc in a dilute nitric acid solution, stirring at room temperature for 1-2 hours, washing with water, and then dispersing in ethanol, adding palmitic acid, titanate coupling agent and sodium p-methoxy fatty amide benzene sulfonate, stirring at 60-65° C. for 2-3 hours, filtering, and drying to obtain pretreated talc; (2) Dispersing the modified nanocellulose in deionized water, adding the pretreated talc powder of step (1), stirring at 70-75° C. for 1-2 h, then adding asbestos fiber and polyvinyl alcohol, stirring for 3-5 h, and drying to obtain modified talc powder.

[0021] By adopting the above technical scheme, dilute nitric acid is used to remove impurities on the surface of talc or perform slight surface etching to increase its surface area and reactivity; then dispersed in ethanol, palmitic acid, titanate coupling agent and sodium p-methoxy fatty amide benzene sulfonate are added. Palmitic acid has good lubricity and dispersibility, which helps talc and other additives to be better dispersed in ethanol, while reducing friction between particles. Titanate coupling agent can react with functional groups such as hydroxyl groups on the surface of talc to form chemical bonds, improve the compatibility and interfacial bonding between talc and polymer matrix, thereby enhancing the mechanical properties and heat resistance of composite materials. Titanate coupling agent can also improve the dispersibility of talc in polymers and reduce agglomeration. Sodium p-methoxy fatty amide benzene sulfonate has good water solubility and dispersibility, reduces the surface tension of the mixture, improves wettability and fluidity, and makes talc more evenly dispersed.

[0022] Modified nanocellulose is dispersed in deionized water to form a nanocellulose dispersion, pretreated talcum powder is added, talcum powder and nanocellulose are fully mixed, nanocellulose coats talcum powder particles to a certain extent, asbestos fiber has high tensile strength, high flexibility, chemical and thermal corrosion resistance, talcum powder can be loaded on the surface of asbestos fiber, modified nanocellulose can coat asbestos fiber, increase the bonding force between talcum powder and asbestos fiber, so that the modified talcum powder has better mechanical properties, heat resistance and chemical stability. Polyvinyl alcohol has good water solubility, film-forming property, bonding property and emulsification property, and cooperates with modified nanocellulose to form a more compact network structure of the mixed system and improve the overall performance. The modified talcum powder obtained by mixing the components has better comprehensive performance and is applied to GMT composite material sheet to increase the mechanical properties, wear resistance and stability of the GMT composite material sheet.

[0023] Preferably, the mass ratio of the talc powder, modified nanocellulose and asbestos fiber is 1:0.7-0.8:0.2-0.3.

[0024] By adopting the above technical scheme, the mass ratio of talcum powder, modified nanocellulose and asbestos fiber is further limited within a certain range, and the obtained modified talcum powder has excellent mechanical properties, talcum powder has high hardness, high strength and good dispersibility, and modified nanocellulose has high crystallinity and excellent mechanical properties, and can form a tight network structure to enhance the strength and toughness of the material. Asbestos fiber has high tensile strength, tensile strength and bending strength, talcum powder can be loaded on the surface of asbestos fiber, and modified nanocellulose can coat talcum powder and asbestos fiber, so that talcum powder and asbestos fiber are tightly bonded, which increases the mechanical strength, heat resistance and overall stability of modified talcum powder. Subsequent application in GMT composite automotive sheet improves the mechanical properties, heat resistance, sound insulation and heat insulation effect and overall quality of the system.

[0025] Preferably, the preparation method of the modified nanocellulose comprises the following steps: dispersing the oxidized nanocellulose in deionized water, adding NN-dimethylformamide, stirring at a temperature of 85-90°C for 3-4h, filtering, and drying to obtain treated oxidized nanocellulose; re-dispersing the treated oxidized nanocellulose in an aqueous sodium periodate solution, reacting at a temperature of 60-70°C for 45-50 min, cooling to room temperature, washing to neutrality, and drying to obtain aldehyde-containing nanocellulose; dispersing the aldehyde-containing nanocellulose in deionized water, adding seaweed fiber, titanium dioxide, and sodium dodecyl sulfate, stirring at a temperature of 70-80°C for 2-3h, and drying to obtain modified nanocellulose.

[0026] By adopting the above technical scheme, the oxidized nanocellulose is dispersed in deionized water, NN-dimethylformamide improves the dispersibility of the nanocellulose and reduces the probability of oxidized nanocellulose agglomeration, the treated oxidized nanocellulose is dispersed in a sodium periodate aqueous solution, aldehyde groups are introduced into the nanocellulose, and aldehyde-containing nanocellulose is obtained.

[0027] The nanocellulose containing aldehyde group is dispersed in deionized water, seaweed fiber, titanium dioxide, sodium lauryl sulfate are added, seaweed fiber has good biocompatibility, toughness, tensile strength, nanocellulose can coat seaweed fiber, increase the mechanical property of system, titanium dioxide has excellent antibacterial, anti-ultraviolet performance, titanium dioxide can be loaded on the surface of seaweed fiber, and nanocellulose makes titanium dioxide and seaweed fiber adhere closely. Sodium lauryl sulfate improves the dispersibility of nanocellulose, seaweed fiber and titanium dioxide in deionized water, makes each mixture evenly dispersed. The modified nanocellulose obtained has good intensity, toughness, good biocompatibility, antibacterial performance and anti-ultraviolet performance, and the corresponding performance of talcum powder is subsequently improved.

[0028] Preferably, the hot melt adhesive layer is polyurethane hot melt adhesive, and the fabric layer is spunbonded non-woven fabric or knitted sponge fabric.

[0029] By adopting the above technical solution, polyurethane hot melt adhesive has excellent bonding performance, which can ensure the firm bonding between the various layers of materials in the car roof. Spunbond non-woven fabric is soft and light, and can be easily processed into various shapes and sizes. It has good wear resistance, sound insulation and heat insulation, and can provide good covering effect and decorativeness.

[0030] Preferably, the composite fiber felt consists of PP fibers and glass fibers.

[0031] By adopting the above technical solution, the PP fiber in the composite fiber felt is the bonding matrix and the glass fiber is the reinforcing material, and the obtained composite fiber felt has good wear resistance, weather resistance, high strength, corrosion resistance and heat resistance.

[0032] In a second aspect, the present application also provides a method for preparing a GMT composite material automobile roof, comprising the following steps: 1) dispersing the expandable microsphere foaming agent and EVA in deionized water, dispersing them evenly to obtain a dispersion; 2) adding modified bamboo fiber, tea tree oil, sodium tripolyphosphate, disodium β-glycerophosphate, lecithin, and modified talc to the dispersion, and ultrasonically vibrating for 1-2 hours to obtain an extract; 3) The composite felt is immersed in the leaching solution and repeatedly turned over and immersed for 30-35 minutes. After the immersion, it is placed at a temperature of 75-80° C. and dried for 6-8 hours to obtain an intermediate; 4) heating and foaming the intermediate at a temperature of 195-200° C. for 40-45 minutes, and then hot pressing and molding at a temperature of 195-200° C. to obtain a GMT composite sheet layer; 5) A hot melt adhesive layer is attached to one side of the GMT composite sheet layer, and the fabric is laid flat on the side of the GMT composite sheet layer with the hot melt adhesive layer, and then hot pressing, punching and assembling are performed to obtain a GMT composite material car roof.

[0033] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing the GMT composite material automobile roof. The obtained GMT composite material automobile roof has good mechanical properties, wear resistance and sealing.

[0034] In summary, this application has the following beneficial effects: 1. The GMT material in this application is a composite material with thermoplastic resin as the matrix and glass fiber felt as the reinforcing skeleton. It has the advantages of light weight, toughness, rigidity, impact resistance and corrosion resistance. The GMT composite sheet layer plays a supporting and protective role in the car roof, can withstand certain external force impact, and improve the ride comfort of the car.

[0035] 2. In the GMT composite board layer of the present application, the composite fiber felt serves as the main reinforcing skeleton, providing the mechanical properties and dimensional stability of the board. The modified bamboo fiber has excellent moisture absorption, air permeability and antibacterial properties, and can be embedded in the composite fiber felt structure to increase the antibacterial and air permeability of the composite fiber felt.

[0036] 3. In the present application, the thickness of the GMT composite material automobile roof after molding is ≤5.5mm. Due to its high specific strength, the GMT composite material has a larger head space compared to the PU roof. Compared with PU, it has lower residual and volatilization of harmful substances such as benzene, aldehyde, and phenol. The GMT composite material has almost no odor, can be repeatedly processed and molded, and the remaining scraps can also be recycled. It has a high degree of design freedom and can achieve a greater molding depth. The "overall flanging" process can be selected, the process is simple, the production efficiency is high, the mold and equipment investment is lower, and the unit processing cost is lower. DETAILED DESCRIPTION

[0037] The present application is further described in detail below in conjunction with embodiments.

[0038] The raw materials used in the examples and comparative examples can all be obtained commercially. Preparation example of modified bamboo fiber

[0039] Preparation Example 1-1 The preparation method of modified bamboo fiber comprises the following steps: (1) 35 kg of bamboo fiber was dispersed in 55 L of 3% NaOH solution, stirred for 2 h, washed with water, and then dispersed in 0.3% aqueous solution of silane coupling agent KH-550, 1.2 kg of calcium carbonate was added, ultrasonicated for 35 min, and dried to obtain pretreated bamboo fiber; (2) Dispersing the modified loofah fiber in 110 L of deionized water, adding the pretreated bamboo fiber of step (1), stirring at 65 °C for 3 h, adding 3 L of glacial acetic acid, chitosan, and 2 kg of sorbitol, continuing to stir for 3 h, drying, and crushing to obtain modified bamboo fiber.

[0040] The mass ratio of bamboo fiber, modified loofah fiber and chitosan is 1:0.5:0.2.

[0041] The preparation method of modified loofah fiber comprises the following steps: crushing 25 kg of loofah fiber, dispersing it in 50 L of sodium hydroxide solution with a mass fraction of 4%, stirring for 12 minutes, washing with water, and then dispersing it in 40 L of hydrogen peroxide, stirring for 30 minutes, washing with water, and then dispersing it in 60 L of deionized water, adding 3 kg of 3-chloro-2-hydroxypropyltrimethylammonium chloride, 6 kg of nano carbon powder, and 3 kg of hydroxypropyl methylcellulose, stirring at a temperature of 75°C for 4 hours, drying, filtering, and obtaining treated loofah fiber, and then spraying the adhesive mixture on the surface of the treated loofah fiber to obtain modified loofah fiber; The adhesive mixture is prepared by mixing 100 L of deionized water, 8 L of ethylene glycol, 20 kg of dextrin glue, 4 kg of lignin sulfonate, and 2 kg of disodium ethylenediaminetetraacetate.

[0042] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no modified loofah fiber is added.

[0043] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (2), chitosan is not added.

[0044] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of bamboo fiber, modified loofah fiber and chitosan is 1:0.6:0.1.

[0045] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of bamboo fiber, modified loofah fiber and chitosan is 1:0.1:0.5.

[0046] Preparation Example 1-6 The difference from Preparation Example 1-1 is that in the preparation method of the modified loofah fiber, no nano carbon powder is added.

[0047] Preparation Example 1-7 The difference from Preparation Example 1-1 is that, in the preparation method of the modified loofah fiber, no dextrin glue is added. Preparation example of modified talc

[0048] Preparation Example 2-1 The preparation method of modified talcum powder comprises the following steps: (1) 30 kg of talc was dispersed in 45 L of a 10% by mass dilute nitric acid solution, stirred at room temperature for 2 h, washed with water, and dispersed in 55 L of ethanol. 2 kg of palmitic acid, 3 kg of a titanate coupling agent, and 1 kg of sodium p-methoxy fatty amide benzene sulfonate were added, stirred at 65 ° C for 3 h, filtered, and dried to obtain pretreated talc; (2) Dispersing the modified nanocellulose in 110 L of deionized water, adding the pretreated talc powder of step (1), stirring at 75 ° C for 2 h, then adding asbestos fiber and 1 kg of polyvinyl alcohol, stirring for 5 h, and drying to obtain modified talc powder.

[0049] The titanate coupling agent is isopropyl tri(dioctyl pyrophosphate) titanate coupling agent.

[0050] The mass ratio of talc, modified nanocellulose and asbestos fiber is 1:0.7:0.3.

[0051] The preparation method of modified nanocellulose comprises the following steps: dispersing 30 kg of oxidized nanocellulose in 50 L of deionized water, adding 5 L of NN-dimethylformamide, stirring at a temperature of 90° C. for 4 hours, filtering, and drying to obtain treated oxidized nanocellulose; re-dispersing the treated oxidized nanocellulose in 100 L of 1 M sodium periodate aqueous solution, reacting at a temperature of 70° C. for 50 minutes, cooling to room temperature, washing to neutrality, and drying to obtain aldehyde-containing nanocellulose; dispersing the aldehyde-containing nanocellulose in 100 L of deionized water, adding 8 kg of seaweed fiber, 6 kg of titanium dioxide, and 2 kg of sodium dodecyl sulfate, stirring at a temperature of 80° C. for 3 hours, and drying to obtain modified nanocellulose.

[0052] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no modified nanocellulose is added.

[0053] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (2), no asbestos fiber is added.

[0054] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of talcum powder, modified nanocellulose and asbestos fiber is 1:0.8:0.2.

[0055] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of talcum powder, modified nanocellulose and asbestos fiber is 1:0.1:0.6.

[0056] Preparation Example 2-6 The difference from Preparation Example 2-1 is that no seaweed fiber is added in the preparation method of modified nanocellulose.

[0057] Preparation Example 2-7 The difference from Preparation Example 2-1 is that in the preparation method of modified nanocellulose, no nano titanium dioxide is added. Example

[0058] Example 1 A GMT composite material automobile roof comprises a GMT composite sheet layer, a hot melt adhesive layer and a fabric layer, wherein the GMT composite sheet layer comprises the following raw materials by weight: 100 kg of composite fiber felt, 22 kg of modified bamboo fiber, 3 kg of tea tree oil, 1 kg of sodium tripolyphosphate, 2 kg of β-glycerophosphate disodium, 0.8 kg of lecithin, 15 kg of modified talcum powder, 6 kg of expandable microsphere foaming agent, and 200 kg of deionized water; The hot melt adhesive layer is polyurethane hot melt adhesive with a thickness of 0.03mm, and the fabric layer is spunbond non-woven fabric with a thickness of 1.2mm; the composite fiber felt is composed of 30kg PP fiber and 60kg glass fiber. After the PP fiber and the glass fiber are mixed, they are combed to make them arranged neatly, and then formed and cured at a curing temperature of 130°C to obtain a composite fiber felt with a thickness of 2mm.

[0059] The method for preparing the GMT composite material automobile roof comprises the following steps: 1) dispersing the expandable microsphere foaming agent and 1 kg of EVA (ethylene-vinyl acetate copolymer) in deionized water, dispersing them evenly to obtain a dispersion; 2) adding modified bamboo fiber, tea tree oil, sodium tripolyphosphate, disodium β-glycerophosphate, lecithin, and modified talc to the dispersion, and ultrasonically vibrating for 2 hours to obtain an extract; 3) The composite felt is immersed in the leaching solution and repeatedly turned over and immersed for 35 minutes. After the immersion, it is placed at a temperature of 80° C. and dried for 8 hours to obtain an intermediate; 4) The intermediate was heated and foamed at a temperature of 200° C. for 45 min, and then hot-pressed at a temperature of 200° C. to obtain a GMT composite sheet layer; the expandable microsphere foaming agent was purchased from Guangdong Yongfeng Chemical Co., Ltd.

[0060] 5) A hot melt adhesive layer is attached to one side of the GMT composite sheet layer, the heating temperature is 130°C, the fabric is laid flat on the side of the GMT composite sheet layer with the hot melt adhesive layer, and then hot-pressed at a temperature of 180°C, punched and assembled to obtain a GMT composite material car roof; During the punching and cutting process, high-pressure water or molds are used to cut the GMT ceiling to ensure that the cutting edges are smooth and meet the design requirements, so as to obtain the required semi-finished ceiling products. The cut scraps are collected, classified and processed. Some scraps may be recycled, while others may need to be disposed of in accordance with relevant regulations.

[0061] Then assemble the accessories, prepare the required accessories, such as lamp fixing frame, harness clip, hook, use positioning pins to accurately position the accessories on the GMT substrate, use gluing or riveting to firmly install the accessories on the GMT substrate, and for the edging position, use the overall flanging method to obtain the GMT composite material car roof.

[0062] The modified bamboo fiber was prepared by using Preparation Example 1-1; and the modified talcum powder was prepared by using Preparation Example 2-1.

[0063] Example 2 A GMT composite material automobile roof, which is different from Example 1 in that the GMT composite sheet layer includes the following raw materials by weight: 90 kg of composite fiber felt, 30 kg of modified bamboo fiber, 5 kg of tea tree oil, 2 kg of sodium tripolyphosphate, 4 kg of β-glycerophosphate disodium, 0.5 kg of lecithin, 20 kg of modified talc, 4 kg of expandable microsphere foaming agent, and 190 kg of deionized water; Among them, the fabric layer is knitted sponge cloth with a thickness of 3.2mm.

[0064] Example 3 A GMT composite material automobile roof, which is different from Example 1 in that the modified bamboo fiber is prepared using Preparation Example 1-2.

[0065] Example 4 A GMT composite material automobile roof is different from Example 1 in that the modified bamboo fiber is prepared using Preparation Examples 1-3.

[0066] Example 5 A GMT composite material automobile roof is different from Example 1 in that the modified bamboo fiber is prepared using Preparation Examples 1-4.

[0067] Example 6 A GMT composite material automobile roof is different from Example 1 in that the modified bamboo fiber is prepared using Preparation Examples 1-5.

[0068] Example 7 A GMT composite material automobile roof is different from Example 1 in that the modified bamboo fiber is prepared using Preparation Examples 1-6.

[0069] Example 8 A GMT composite material automobile roof, which is different from Example 1 in that the modified bamboo fiber is prepared using Preparation Examples 1-7.

[0070] Example 9 A GMT composite material automobile roof, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Example 2-2.

[0071] Example 10 A GMT composite material automobile roof, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Example 2-3.

[0072] Embodiment 11 A GMT composite material automobile roof, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Examples 2-4.

[0073] Example 12 A GMT composite material automobile roof, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Examples 2-5.

[0074] Example 13 A GMT composite material automobile roof, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Examples 2-6.

[0075] Embodiment 14 A GMT composite material automobile roof, which is different from Example 1 in that the modified talcum powder is prepared using Preparation Examples 2-7. Comparative Example

[0076] Comparative Example 1 A GMT composite material automobile roof, which differs from Example 1 in that modified bamboo fiber is not added.

[0077] Comparative Example 2 A GMT composite material automobile roof, which is different from Example 1 in that the modified bamboo fiber is replaced by an equal amount of bamboo fiber.

[0078] Comparative Example 3 A GMT composite material automobile roof, which differs from Example 1 in that modified talcum powder is not added.

[0079] Comparative Example 4 A GMT composite material automobile roof, which is different from Example 1 in that the modified talcum powder is replaced by an equal amount of talcum powder.

[0080] Performance testing The GMT composite material automobile ceilings prepared in Examples 1-14 and Comparative Examples 1-4 were subjected to performance tests; The tensile strength and elongation at break are tested according to GB / T 1499-2005, the flexural strength is tested according to GB / T 9341-2008, and the Shore hardness (type D) is tested according to ISO 7619-97.

[0081] Using a punching tester, the substrate is clamped between two steel plates with a hole in the middle of the tester. The punch and the substrate are kept perpendicular to each other to test the impact strength of the sample. The test results are shown in Table 1.

[0082] Table 1 Test data of embodiments and comparative examples

[0083] As can be seen from Table 1, the GMT composite material automobile roof prepared in Examples 1-2 of the present application has good hardness, mechanical properties and durability, wherein the hardness of Example 1 is 78, the tensile strength in the original state is 29.8MPa, the tensile strength after aging at 120°C for 500h is 27.7MPa, the elongation at break is 10.6%, the impact strength is 20.6MPa, and the bending strength is 18.9MPa. This indicates that the prepared GMT composite material automobile roof has excellent mechanical properties, aging resistance, and temperature resistance, and each component is evenly mixed, and the obtained GMT composite sheet layer has good mechanical properties, so that the automobile roof has excellent aging resistance.

[0084] In the preparation method of the modified bamboo fiber of Examples 3-4, modified loofah fiber and chitosan are not added respectively. In Examples 5-6, the mass ratio of bamboo fiber, modified loofah fiber and chitosan is changed. It can be seen from Table 1 that the performance test results of hardness, tensile strength in the original state, tensile strength after aging at 120°C for 500h, elongation at break, impact strength and flexural strength of Examples 3-4 are worse than those of Examples 1-2 and Example 5. The above performance effects of Example 6 are better than those of Examples 3-4, but worse than those of Examples 1-2 and Example 5, indicating that the modified loofah fiber and bamboo fiber can be adsorbed and combined with each other, thereby increasing the mechanical properties and adsorption of the bamboo fiber. Chitosan makes the bamboo fiber and the modified loofah fiber bond tightly, increasing the flexibility of the modified bamboo fiber, and is subsequently applied to the GMT composite material board to increase the mechanical strength, weather resistance and antibacterial properties of the GMT composite material board, thereby extending the service life of the board.

[0085] In the preparation method of the modified loofah fiber of Examples 7-8, nano carbon powder and dextrin glue are not added respectively. As can be seen from Table 1, the performance test results of hardness, tensile strength in the original state, tensile strength after aging at 120°C for 500h, elongation at break, impact strength, and flexural strength of Examples 7-8 are better than those of Example 3, but worse than those of Examples 1-2, indicating that the nano carbon powder has good mechanical properties, thermal stability and conductive properties, can be loaded on the surface and pores of the loofah fiber, effectively fill the gaps between the fibers, form a more compact structure, and increase the strength, wear resistance and toughness of the loofah fiber; the adhesive mixture is sprayed on the surface of the treated loofah fiber, and the dextrin glue has a high viscosity, so that the loofah fiber and the nano carbon powder are tightly bonded, and are subsequently applied to bamboo fiber to improve the bonding force between the bamboo fiber and other components, which helps to improve the performance of the GMT composite material sheet.

[0086] In the preparation method of the modified talc powder of Examples 9-10, modified nanocellulose and asbestos fiber are not added respectively. In Examples 11-12, the mass ratio of talc powder, modified nanocellulose and asbestos fiber is changed. It can be seen from Table 1 that the performance test results of hardness, original tensile strength, tensile strength after aging at 120°C for 500h, elongation at break, impact strength and flexural strength of Examples 9-10 are worse than those of Examples 1-2 and Example 11. The above performance effects of Example 12 are better than those of Examples 9-10, but worse than those of Examples 1-2 and Example 11, indicating that asbestos fiber has high tensile strength, tensile strength and flexural strength, talc powder can be loaded on the surface of asbestos fiber, and modified nanocellulose can coat talc powder and asbestos fiber, so that talc powder and asbestos fiber are closely bonded, thereby increasing the mechanical strength, heat resistance and overall stability of the modified talc powder; it is subsequently applied to GMT composite automotive sheet to improve the mechanical properties, heat resistance, sound insulation and heat insulation effects and overall quality of the system.

[0087] In the preparation methods of modified nanocellulose of Examples 13-14, seaweed fiber and nano-titanium dioxide are not added respectively. As can be seen from Table 1, the performance test results of hardness, tensile strength in the original state, tensile strength after aging at 120°C for 500h, elongation at break, impact strength and bending strength of Examples 13-14 are better than those of Example 9, but worse than those of Examples 1-2, indicating that seaweed fiber has good biocompatibility, toughness and tensile strength, nanocellulose can coat seaweed fiber to increase the mechanical properties of the system, titanium dioxide has excellent antibacterial and anti-ultraviolet properties, titanium dioxide can be loaded on the surface of seaweed fiber, and nanocellulose makes titanium dioxide and seaweed fiber bond tightly.

[0088] No modified bamboo fiber or modified talcum powder is added to Comparative Example 1 and Comparative Example 3, respectively. As can be seen from Table 1, compared with Example 1, the performance test results of hardness, tensile strength in the original state, tensile strength after aging at 120°C for 500h, elongation at break, impact strength, and flexural strength of Comparative Example 1 and Comparative Example 3 are significantly worse than those of Examples 1-2, indicating that the modified bamboo fiber has excellent moisture absorption and air permeability and antibacterial properties, can be embedded in the composite fiber felt structure, and increase the antibacterial and air permeability of the composite fiber felt; modified talcum powder has good filling properties, reduces the density and cost of the board, while improving the hardness and wear resistance of the board, and improving its compatibility with the GMT matrix.

[0089] In Comparative Examples 2 and 4, the modified bamboo fiber is replaced by an equal amount of bamboo fiber, and the modified talcum powder is replaced by an equal amount of talcum powder. As can be seen from Table 1, the performance test results of hardness, tensile strength in the original state, tensile strength after aging at 120°C for 500h, elongation at break, impact strength, and flexural strength of Comparative Examples 2 and 4 are significantly worse than those of Examples 1-2, but better than those of Comparative Examples 1 and 3, indicating that the modified bamboo fiber and modified talcum powder of the present application have good mechanical properties, mechanical properties, and aging resistance, and maintain the structural strength and performance stability of the automobile roof.

[0090] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A GMT composite material automobile roof, comprising a GMT composite sheet layer, a hot melt adhesive layer and a fabric layer, characterized in that: The GMT composite board layer includes the following raw materials, measured in parts by weight: 90-100 parts of composite fiber felt, 22-30 parts of modified bamboo fiber, 3-5 parts of tea tree oil, 1-2 parts of sodium tripolyphosphate, 2-4 parts of β-glycerophosphate disodium, 0.5-0.8 parts of lecithin, 15-20 parts of modified talc, 4-6 parts of expandable microsphere foaming agent, and 190-200 parts of deionized water.

2. The GMT composite material automobile roof according to claim 1, characterized in that: The preparation method of the modified bamboo fiber comprises the following steps: (1) dispersing the bamboo fiber in a NaOH solution, stirring for 1-2 hours, washing with water, and then dispersing the bamboo fiber in a silane coupling agent aqueous solution, adding calcium carbonate, ultrasonicating for 30-35 minutes, and drying to obtain pretreated bamboo fiber; (2) Dispersing the modified loofah fiber in deionized water, adding the pretreated bamboo fiber of step (1), stirring at a temperature of 60-65° C. for 2-3 h, adding glacial acetic acid, chitosan, and sorbitol, continuing to stir for 2-3 h, drying, and crushing to obtain modified bamboo fiber.

3. The GMT composite material automobile roof according to claim 2, characterized in that: The mass ratio of the bamboo fiber, the modified loofah fiber and the chitosan is 1:0.5-0.6:0.1-0.

2.

4. The GMT composite material automobile roof according to claim 2, characterized in that: The preparation method of the modified loofah fiber comprises the following steps: crushing the loofah fiber, dispersing it in a sodium hydroxide solution, stirring for 10-12 minutes, washing with water, dispersing it in hydrogen peroxide, stirring for 25-30 minutes, washing with water, dispersing it in deionized water, adding 3-chloro-2-hydroxypropyltrimethylammonium chloride, nano carbon powder, and hydroxypropyl methylcellulose, stirring for 3-4 hours at a temperature of 70-75° C., drying, filtering, obtaining treated loofah fiber, and then spraying an adhesive mixture on the surface of the treated loofah fiber to obtain modified loofah fiber; The adhesive mixture is prepared by mixing deionized water, ethylene glycol, dextrin glue, lignin sulfonate and disodium ethylenediaminetetraacetate.

5. The GMT composite material automobile roof according to claim 1, characterized in that: The preparation method of the modified talcum powder comprises the following steps: (1) dispersing talc in a dilute nitric acid solution, stirring at room temperature for 1-2 hours, washing with water, and then dispersing in ethanol, adding palmitic acid, titanate coupling agent and sodium p-methoxy fatty amide benzene sulfonate, stirring at 60-65° C. for 2-3 hours, filtering, and drying to obtain pretreated talc; (2) Dispersing the modified nanocellulose in deionized water, adding the pretreated talc powder of step (1), stirring at 70-75° C. for 1-2 h, then adding asbestos fiber and polyvinyl alcohol, stirring for 3-5 h, and drying to obtain modified talc powder.

6. The GMT composite material automobile roof according to claim 5, characterized in that: The mass ratio of the talcum powder, modified nanocellulose and asbestos fiber is 1:0.7-0.8:0.2-0.

3.

7. The GMT composite material automobile roof according to claim 5, characterized in that: The preparation method of the modified nanocellulose comprises the following steps: dispersing oxidized nanocellulose in deionized water, adding NN-dimethylformamide, stirring at a temperature of 85-90°C for 3-4 hours, filtering, and drying to obtain treated oxidized nanocellulose; re-dispersing the treated oxidized nanocellulose in a sodium periodate aqueous solution, reacting at a temperature of 60-70°C for 45-50 minutes, cooling to room temperature, washing to neutrality, and drying to obtain aldehyde-containing nanocellulose; dispersing the aldehyde-containing nanocellulose in deionized water, adding seaweed fiber, titanium dioxide, and sodium dodecyl sulfate, stirring at a temperature of 70-80°C for 2-3 hours, and drying to obtain modified nanocellulose.

8. The GMT composite material automobile roof according to claim 1, characterized in that: The hot melt adhesive layer is polyurethane hot melt adhesive, and the fabric layer is spunbonded non-woven fabric or knitted sponge fabric.

9. The GMT composite material automobile roof according to claim 1, characterized in that: The composite fiber felt consists of PP fiber and glass fiber.

10. The method for preparing a GMT composite material automobile roof according to claim 1, characterized in that: The steps include: 1) dispersing the expandable microsphere foaming agent and EVA in deionized water, dispersing them evenly to obtain a dispersion; 2) adding modified bamboo fiber, tea tree oil, sodium tripolyphosphate, disodium β-glycerophosphate, lecithin, and modified talc to the dispersion, and ultrasonically vibrating for 1-2 hours to obtain an extract; 3) The composite felt is immersed in the leaching solution and repeatedly turned over and immersed for 30-35 minutes. After the immersion, it is placed at a temperature of 75-80° C. and dried for 6-8 hours to obtain an intermediate; 4) heating and foaming the intermediate at a temperature of 195-200° C. for 40-45 minutes, and then hot pressing and molding at a temperature of 195-200° C. to obtain a GMT composite sheet layer; 5) A hot melt adhesive layer is attached to one side of the GMT composite sheet layer, and the fabric is laid flat on the side of the GMT composite sheet layer with the hot melt adhesive layer, and then hot pressing, punching and assembling are performed to obtain a GMT composite material car roof.

Citation Information

Patent Citations

  • Preparation method of ultra-light and high-strength GMT composite board for automotive interior and exterior decorative parts

    CN108215443A

  • GMT plate and preparation method and application thereof

    CN112521683A

  • PP / ASA alloy material for camping car tail baffle and manufacturing method of PP / ASA alloy material

    CN116622161A

  • Anti-tear mesh cloth for sports shoes and preparation method thereof

    CN117468241A

  • Secondary foaming thermal insulation material and preparation method thereof

    CN117484990A

Cited By

  • Environment-friendly composite material for automobile and preparation method of environment-friendly composite material

    CN120269897A

  • Environmentally friendly composite material for automobiles and preparation method thereof

    CN120269897B

  • Glue-free low-odor automobile roof and preparation method thereof

    CN122100600A